Hydrodynamic coefficients of a yawed square cylinder in oscillatory flows. (15th January 2017) - Lou, X.; Zhou, T.; Cheng, L.
Abstract: The effect of yaw angle ( α ) on hydrodynamic forces and vortex shedding regime classification of a square cylinder oscillating in still water is examined. The Independent Principle (IP), which states that the Strouhal number and the drag coefficient are independent of α if the normal velocity component is used, was examined in oscillatory flows. Hydrodynamic forces were measured over a Keulegan-Carpenter number (KC) range of 3–30 and a Stokes parameter ( β ) range of 500–1600. For KC=8 - 20, the drag coefficient at α = 45° is about 46% higher than that at α = 0°, indicating the invalidity of the IP in oscillatory flow over this KC range. The inertia coefficient decreases with the increase of the yaw angle, except for KC = 8–20, where the sudden drop in the distribution is absent at α = 45°. Apart from this KC range, the inertia coefficient follows the IP better than the drag coefficient does. In addition, the lift coefficient increases with the increase of cylinder yaw angle. The results of the lift force spectra and the lift coefficients imply that the existence of the cylinder yaw angle has an intensified effect on the vortex shedding process around a square cylinder in oscillatory flows. Highlights: IP of a square cylinder wake examined in oscillatory flows. The hydrodynamic forces of a square cylinder is sensitive to yaw angle. Significant differences are observed for KC in the range of 8–20. Yaw angle does not influence the classification of flow regime classification.